Stroke and liminality: narratives of reconfiguring identity after stroke and their implications for person-centred stroke care - Hall, Joseph; van Wijck, Frederike; Kroll, Thilo; Bassil-Morozow, Helena (Frontiers in Rehabilitation Sciences, 2024)
BackgroundThe complex physical, cognitive, and psychological consequences of stroke can disrupt a survivor's sense of pre-stroke normality and identity. This can have a substantial impact on their individual and social lives. Individual reports about life after stroke have improved our understanding of this impact. However, stroke support systems, struggling with increased demands due to a growing stroke population and guideline requirements, require deeper insights based on synthesised narratives into what can enable stroke survivors to rebuild their lives and identities positively to provide person-centred care.MethodsA qualitative study using Charmaz's Constructivist Grounded Theory (GT) method. Semi-structured interviews lasting 60–90 min were conducted. These interviews were held at least 12 months post-stroke.FindingsThirty participants were interviewed from across the UK (14 women, 16 men; aged 31–86; 1–25 years post-stroke). Participants reported the disruption stroke could cause to their sense of identity. The concept of liminality, that describes the ambiguous, transformative state between two distinct stages, where an individual or group exists “betwixt and between” stable conditions, explains the challenge to identity post-stroke. Participants reported developing an uncertain sense of identity as they struggled to structure identity in the same way they did before stroke. This is because the participants' characteristics, traits, hobbies, or future life plans, as well as social relationships and roles, were affected by stroke. Subsequently, participants began a process of reconfiguring their identity, an often-long-term process that involved coming to terms with, and integrating, the impact of stroke on their lives. As a result, participants could enter an indefinite period of sustained liminality as they contend with long-term change and continued uncertainty.ConclusionThe concept of liminality, which emerged from individual stroke narratives for the first time, conveyed the adaptive and enduring nature of a stroke survivor's journey. Post-stroke liminality may continue indefinitely, sustained by a survivor's subjective individual and social situation. This new insight justifies the urgent call for long-term rehabilitation and support that is tailored towards the unique nature of a survivor's circumstances. Further work is required to understand how tailored, long-term and person-centred support can encourage survivors to positively reconfigure their identity.